Extreme kinematic misalignment in IllustrisTNG galaxies: the origin, structure, and internal dynamics of galaxies with a large-scale counterrotation. Issue 3 (27th October 2020) - Khoperskov, Sergey; Zinchenko, Igor; Avramov, Branislav; Khrapov, Sergey; Berczik, Peter; Saburova, Anna; Ishchenko, Marina; Khoperskov, Alexander; Pulsoni, Claudia; Venichenko, Yulia; Bizyaev, Dmitry; Moiseev, Alexei
ABSTRACT: We provide an in-deep analysis of 25 galaxies with substantial counterrotation from IllustrisTNG100 simulations in the stellar mass range 2×10 9 −3×10 10 M⊙ . The counterrotation is a result of an external gas infall ≈2–8 Gyr ago. The infall leads to the removal of pre-existing gas, which is captured and mixed together with the infalling component. This mixture ends up in the counterrotating gaseous disc where ${≈}90{{\ \rm per\ cent}}$ of counterrotating stars formed in-situ. During the early phases of the infall, gas can be found in extended structures which, in some galaxies, are similar to (nearly-) polar ring-like components. We suggest that the AGN activity does not cause the counterrotation, although it is efficiently triggered by the retrograde gas infall, and it correlates well with the misaligned component appearance. We also find the vertical-to-radial velocity dispersion ratio above unity implying the importance of misalignment in shaping the velocity ellipsoids.